Living Arrangement: a Contributor to Vascular Disease in Asymptomatic African American Women - Meldra Hall; Elizabeth Ofili; Rigobert Lapu-Bula; Ernest Alema-Mensah; Stephanie Miles-Richardson (Georgia Southern University, 2019)
Background: Diminished social support has shown to lead to worse cardiovascular outcomes and since cardiovascular disease (CVD) is the leading cause of death in the United States (U.S.), it is critical to non-invasively study its precursor- vascular disease (VD). Assessing the impact social support has on vascular outcomes can unveil potential CVD susceptibilities in at-risk populations. African American women exhibit the greatest burden of CVD morbidity and mortality; therefore, the purpose of this study is to examine the association between living arrangement/social support and impaired vascular function in asymptomatic African American women. Methods: Vascular function was assessed by a non-invasive screening tool, HDI/PulseWave CR-2000, during screenings at community outreach events on participants clinically free of CVD. Vascular disease was defined as abnormal/impaired vascular function. Living arrangement, a binary variable (living with someone/living alone), was determined by survey responses (N=67) and represented social support. Multivariable analyses were used to estimate adjusted odds ratios (AORs) and 95% confidence intervals (95% CIs) to determine the association between living arrangement and vascular disease after controlling for confounders. Analyses were conducted using SAS 9.2. Results: Of those who lived alone, 82% had vascular disease (p=0.03). After adjusting for family CVD, and other CVD risk factors, those who lived with a spouse/partner or relative were 78% (p=0.04) less likely to develop vascular disease (AOR=0.22; 95% CI=0.05, 0.98). Conclusions: Our study provides preliminary evidence to suggest that among African American women, clinically free of CVD, living arrangement is associated with vascular disease. While living alone may place individuals at an increased risk of CVD because of the association, living with a spouse/partner or relative may act as a protective factor against vascular disease and reduce the risk of CVD. Public health practitioners may use individuals' living arrangement as preventive measure for CVD risk. Keywords: Living arrangement, social support, vascular disease, arterial elasticity, vascular function